Answer:
Step-by-step explanation:
(-4+4)/2 = 0/2 = 0
(4+8)/2 =12/2= 6
(0, 6)
Answer:
.
Step-by-step explanation:
Given : phrase the quotient of 3 and z.
To find :what is the algebraic expression for the following word phrase .
Solution : We have given
Phrase the quotient of 3 and z.
We get the quotient when we divide the two terms.
So , We need to divide 3 and z to get the quotient.
Quotient = .
Therefore, .
The algebraicexpression for the word phrase "the quotient of 3 and z" is 3/z or 3 ÷ z.
We have,
The word "quotient" indicates division, so we know that we need to perform a division operation.
In this case, we are dividing the number 3 by the variable z.
In algebraic notation, the division is typically represented using the forward-slash (/) or the division symbol (÷).
Therefore, we can write "the quotient of 3 and z" as 3/z or 3 ÷ z.
Both expressions convey the idea that we are dividing 3 by the value of z.
Thus,
The algebraicexpression for the word phrase "the quotient of 3 and z" is 3/z or 3 ÷ z.
Learn more about expressions here:
#SPJ6
Answer:
see explanation
Step-by-step explanation:
150° is in the second quadrant.
To find the reference angle in the first quadrant subtract from 180°
reference angle = 180° - 150° = 30°
Answer:
-180-x
Step-by-step explanation:
1. t^2 +2t - 48 =
2. t^2 + 16t - 48 =
3. t^2 - 13t - 48 =
4. x^2 - 17x + 42 =
5. x^2 + 13x - 30 =